The Role of Hyperbaric Oxygen to Platelet Aggregation in Diabetic Patients Type II (NIDDM) - Widiyanti, Prihartini (Indonesian Journal of Tropical and Infectious Disease, 2010)
Prevalency of Diabetes Mellitus in Indonesia has tendency to be increased from year to year. Hyperbaric Oxygenation (HBO) has been used as treatment of Diabetes Mellitus's complication especially diabetic gangrene. But the effect of HBO to the rheology's disfunction especially platelet's aggregation in the patients of NIDDM was investigated. The randomized pretest-posttest design was used in this study. An experimental laboratory study was performed at Naval Health Institution in Surabaya. 32 patients of NIDDM,women, 40–75 years old, normal physic's diagnosa, normal thorak's photo, normal EKG, normal Ear Nose and Throat, Diabetes Mellitus's family's record, normal weight (BMI), blood glucose level didn't exceed 400 mg/dl (including controlled DM FBG < 120 mg/dl dan 2 H BG < 160 mg/dl), NIDDM, normal level of HbA1c (4–5,9), as long as this research they couldn't take their Oral Hipoglikemic Agent, Oral Anti Trombotic, vitamin C and vitamin E. They are divided into 2 group: group of HBO 100% O 2,4 ATA for 3x30 minutes with interval  5 minutes to inhalate air once a day daily for 5 days subsequently and the extraction of data (PAT) had been held before oxygenation hyperbaric therapy at the first day and the end of fifth days, in control group only giving 20% O2 with the pressure 1 ATA for 90 minutes once a day daily for 5 days subsequently and the extraction of data (PAT) had been held before normoxia normobaric therapy at the first day and the end of fifth days. The results were significant decrease of the platelet's aggregation level especially percent of aggregation after 5 days from 76,56 ± 8,06 become 69,13 ± 6,03. Latent Periode has also decrease from 28,75 ± 3,87 become 25,75 ± 2,82. Speed of Aggregation has also decrease from 66,25 ± 3,17 become 62,50 ± 3,44. Index of Aggregation has also decrease from 0,763 ± 0,071 become 0,581 ± 0,083. Using paired t-test, it could be seen the decrease of Latent Periode (p= 0,001) and index of aggregation (p= 0,000) significantly after exposure of oxygenation hyperbaric HBO 2,4 ATA 100% O 3í—30 minutes with interval 5 minutes inhalate air once a day for 5 days,subsequently. Speed of aggregation (p = 0,022) and percent of aggregation (p= 0,013) are nonsignificantly. The conclusion of this research is that oxygenation hyperbaric 2,4 ATA 100% O2 3í—30 minutes with interval 5 minutes inhalate air once a day for 5 days,subsequently could decrease latent periode, speed of aggregation,  index of aggregation and percent of aggregation in NIDDM